Sociodemographic and clinical variables associated with discharge under compulsory treatment orders. (April 2021) - Dey, Sangeeta; Mellsop, Graham; Obertova, Zuzana; Jenkins, Matthew
Objective: To document the sociodemographic and clinical variables associated with discharge under compulsory treatment orders in patients with schizophrenia or related disorders. Method: Information on various sociodemographic and clinical variables were extracted from the clinical files of 349 patients discharged from an adult (age 18–65) inpatient psychiatric unit with diagnoses of schizophrenia or related disorders. Univariate and multiple logistic regression analyses with legal compulsion (compulsory versus voluntary) as outcomes were applied. Results: Two hundred of the 349 discharged patients were placed under compulsory treatment orders. In the univariate logistic regression analysis, unemployment, diagnosis of schizophrenia, forensic history, dosage of antipsychotics, prescription and frequency of injectable antipsychotics, polypharmacy and a hospital stay of more than 28 days were associated with compulsory status. Being married or in partnership and living with partner was associated with voluntary status. Multiple regression models respectively confirmed most of these relationships observed in the univariate analyses. Conclusion: Clarification of the apparent drivers for compulsory treatment may help thoughtful reductions in the use of compulsion.